2019
DOI: 10.1111/iej.13197
|View full text |Cite
|
Sign up to set email alerts
|

Potential immunomodulatory effects of stem cells from the apical papilla on Treg conversion in tissue regeneration for regenerative endodontic treatment

Abstract: Aim To evaluate the expression of Foxp3‐positive lymphocytes around newly formed tissue after regenerative endodontic treatment (RET) in vivo and investigate the effects of stem cells from the apical papilla (SCAP) on the conversion of CD4+CD25− T cells to CD4+CD25+Foxp3+ regulatory T cells (Tregs) in vitro. Methodology Three 6‐month‐old beagles with nine doubled‐rooted premolars in each dog were randomly assigned to the RET group and the control group. RET was performed after apical periodontitis had been ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Thus, the balance between the host pro-inflammatory and anti-inflammatory responses supposedly determines the progression and outcome of apical periodontitis, which is regulated by different types of CD4 + T helper cells, including at least Th1, Th2, Th17, and Treg cells ( 57 ). As a potential protective subset of CD4 + T cells, accumulating studies have revealed that the beneficial role of Treg cells in restricting the overactivity of the periapical inflammatory response ( 58 , 59 ).…”
Section: Distribution and Functions Of Treg Cells In Oral Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the balance between the host pro-inflammatory and anti-inflammatory responses supposedly determines the progression and outcome of apical periodontitis, which is regulated by different types of CD4 + T helper cells, including at least Th1, Th2, Th17, and Treg cells ( 57 ). As a potential protective subset of CD4 + T cells, accumulating studies have revealed that the beneficial role of Treg cells in restricting the overactivity of the periapical inflammatory response ( 58 , 59 ).…”
Section: Distribution and Functions Of Treg Cells In Oral Diseasesmentioning
confidence: 99%
“…In vitro, stem cells from the apical papilla (SCAP) promoted the conversion of pro-inflammatory T cells to Treg cells. It may suggest that the anti-inflammatory and anti-apoptotic abilities of upregulated Treg cells promote successful tissue repair and regeneration via releasing more cytokines and pro-healing growth factors, which may create an appropriate immune microenvironment for tissue regeneration ( 59 ).…”
Section: Distribution and Functions Of Treg Cells In Oral Diseasesmentioning
confidence: 99%
“…From Liu et al . (2019) – ‘Fig. 2 provides the key information in the legend with scale bars on images.…”
Section: Introductionmentioning
confidence: 99%
“…From Liu et al . (2019) – ‘Pulp‐like tissues and free cellular cementum‐like tissues in the root canal and cellular cementum‐like tissues on the root wall were observed. Inflammatory cells were present in the periapical area and root canal together with newly formed tissue, and most were lymphocytes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the SCAP within the apical papilla, it became clear that multipotent SCAP are highly suitable for osteogenic, adipogenic and chondrogenic differentiation ( Huang G. T. J. et al, 2009 ). Together with their immunomodulatory capacity ( Gaudin et al, 2018 ; Liu et al, 2019 ; Fehrmann et al, 2020 ), SCAP have a high potential for implementation in tissue regeneration. This offered the research community an easily accessible mesenchymal stem cell source with low ethical considerations.…”
Section: Introductionmentioning
confidence: 99%